(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article examines the growing role of educational technologies in teaching listening comprehension in English language learning. Rapid digitalization has transformed traditional teaching methods, providing teachers and learners with new opportunities such as mobile applications, artificial intelligence tools, video-based platforms, interactive learning management systems, and authentic audio resources. This paper discusses the pedagogical benefits of technology integration, identifies the most effective digital tools for improving listening skills, and offers practical strategies for classroom implementation. The findings show that technology not only enhances learner motivation but also improves listening accuracy, learner autonomy, comprehension speed, and overall communicative competence. The article concludes with recommendations for teachers on how to effectively incorporate technology into their listening instruction to achieve meaningful learning outcomes.